SADARI (Periksa Payudara Sendiri) : Pengetahuan dan Perilaku Remaja kota dan Desa di Provinsi Papua - Asti, Helen Try Juni; Asriati, Asriati (Jurnal Ilmiah Global Education, 2024)
Breast cancer is still a serious problem in both developed and developing countries. Cancer is the highest cause of death in the world. In Indonesia, breast cancer is also the type of cancer that contributes the highest to the female cancer prevalence rate. The low level of early detection efforts by self-examination of the breasts and clinical breast examinations is the cause of the increase in breast cancer. Leading to an increase in the death rate. The aim of this research is to identify knowledge and behavior of BSE (breast self- examination) among urban and rural teenage girls in Papua Province. This research method uses a cross sectional study design. The sample in this study was 185 urban and rural teenage girls. Data analysis used the Mann Whitney U statistical test to see differences in BSE knowledge and behavior in urban n rural teenage girls. The research results showed that the majority of urban teenage girls’ knowledge level was in the high category, while the majority of rural teenage girls were in the low category. While the behavior of urban teenage girls tended to be more obedient in doing BSE (breast self- examination) compared to rural teenage girls. Bivariate analysis show that there is a difference in the level of knowledge between urban and rural teenage girls regarding BSE (breast self- examination) with a p-value (0,000) < 0,05 and there is also difference in BSE (breast self- examination) behavior among urban and rural teenage girls with p-value (0.016)<0.05.